Hubungan Manajemen Laba (Earning Management) dengan Kinerja Operasi dan Return Saham di Sekitar IPO - Saiful, Saiful (The Indonesian Journal of Accounting Research, 2004)
Previous researchers found some empirical evidences of earnings management surrounding initial public offering (IPO). They also found that operating performance and stock return after IPO is underperformed.Â  The underperformed of operating performances and stock return associated with earnings management surrounding IPO. The purpose of this research is to examine earnings management surrounding IPO, operating performances, stock return, and the association of earnings management surrounding IPO with operating performance and stock return in Indonesia.This study found that earnings management had occurred in years surrounding IPO that is in the second year before IPO, in the year IPO taking place, and in the second year after IPO. This study also found that operating performance and stock return after IPO are underperformed. The study also found the association between earnings management surrounding IPO and operating performance. The study did not find empirical evidence about association between earnings management surroundings IPO and stock return.The author concludes that managements take future earnings to increase current earnings to maximize their utilities but investors and other market participants are unable to understand earnings management surrounding IPO.Â  This condition may be affected by unsophisticated investors and other market participants in emerging capital market.